The Impact of Augmented Reality Media on High School Students’ Critical Thinking Skills in Physics - Hasan, Muh Iqbal; Kaharuddin Arafah; Mutahharah Hasyim (Universitas Muhammadiyah Makassar, 2025)
The rapid development of digital technologies has created new opportunities to enhance learning processes in science education, particularly in physics, which is often perceived as abstract and conceptually difficult. Students frequently struggle to interpret invisible phenomena such as electric charges and fields, leading to misconceptions that hinder higher-order thinking skills. In response to this challenge, augmented reality (AR) has emerged as a promising instructional tool capable of visualizing abstract concepts and fostering active engagement. This study aimed to investigate the effect of AR-based learning media on students’ critical thinking skills in high school physics. A quasi-experimental design with a posttest-only nonequivalent control group was employed, involving two intact Grade XII classes: the experimental group (n = 32) received instruction using PyLo-AR, while the control group (n = 33) was taught through conventional methods. Data were collected using a validated essay test that measured four critical thinking indicators: interpretation, analysis, evaluation, and inference. The results of descriptive analysis showed that the experimental group achieved a higher mean score (M = 14.56, SD = 2.03) compared to the control group (M = 12.94, SD = 1.95). Inferential analysis using the independent samples t-test indicated a statistically significant difference between the groups (p = 0.002), confirming the effectiveness of AR-based instruction. The novelty of this research lies in its focus on critical thinking outcomes rather than solely on conceptual understanding or motivation. In conclusion, AR-based media not only improve students’ mastery of abstract physics concepts but also strengthen their critical thinking skills, offering meaningful contributions to the advancement of physics education in the twenty-first century.